Atmosphere and room temperature plasma alters the m6A methylome profiles and regulates gene expression associated with color mutation in clownfish (Amphiprion ocellaris) - He, Li-Bin; Luo, Hui-Yu; Zheng, Le-Yun (Frontiers in Marine Science, 2023)
Since the release of the movie Finding Nemo, clownfish have been known and loved by many people. Clownfish have a very vivid skin color and extreme ornamental value. However, there are few species of clownfish, which greatly limits the breeding of new varieties. In this study, the Atmosphere and room temperature plasma (ARTP) method was used to treat clownfish-fertilized eggs and successfully screened out mutants that exhibited a skin color change from black to red in their offspring. To elucidate the molecular mechanism underlying this color mutation, more than 17,000 methylated peaks were obtained via m6A-specific methylated RNA immunoprecipitation with next-generation sequencing (MeRIP-seq). These modification sites were mainly distributed around stop codons, and the number of corresponding genes exceeded 10,000. Further RNA sequencing (RNA-seq) of clownfish before and after the mutation was performed identified 883 genes that exhibited significant differences between the two samples, among which 152 interaction genes showed significant differences in the m6A methylated level and gene expression level. The results of a functional analysis showed that the PI3K-Akt pathway and its related signal pathways may play an important role in skin color change. In particular, genes such as MAP2K1, IGF1, and FGF1 may play key roles in the accumulation of melanin in clownfish, and the homeobox-protein-encoding EMX2 and MEOX2 genes may be important for determining the regions of accumulation of this skin pigment. Our results provide a new reference for the genetic breeding of clownfish and lay a foundation for further understanding the molecular mechanism underlying body color changes in clownfish.